Doing better with less energy [fuel-efficient power generation]. - Sathbye, J. (IEEE spectrum)
The authors describe how many fuel-efficient coal-fired power generation technologies can be adopted at reduced net cost, but argue that, unless barriers to innovation are removed, their adoption will be far from automatic